Home as Found Authority and Genealogy in Nineteenth-Century American Literature - Burbank, Augustus Ripley, 1817-1902.; Project Muse.
Diary (240 pages).
Pioneer, businessman, and politician of Washington and Oregon.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Description based on print version record.
Keywords: Politicians; Pioneers; Businessmen; Electronic books